Characterization of N-terminally mutated cardiac Na+ channels associated with long QT syndrome 3 and Brugada syndrome - Gütter, Christian; Benndorf, Klaus; Zimmer, Thomas (Frontiers in Physiology, 2013)
Mutations in SCN5A, the gene encoding the cardiac voltage-gated Na+ channel hNav1.5, can result in life-threatening arrhythmias including long QT syndrome 3 (LQT3) and Brugada syndrome (BrS). Numerous mutant hNav1.5 channels have been characterized upon heterologous expression and patch-clamp recordings during the last decade. These studies revealed functionally important regions in hNav1.5 and provided insight into gain-of-function or loss-of-function channel defects underlying LQT3 or BrS, respectively. The N-terminal region of hNav1.5, however, has not yet been investigated in detail, although several mutations were reported in the literature. In the present study we investigated three mutant channels, previously associated with LQT3 (G9V, R18W, V125L), and six mutant channels, associated with BrS (R18Q, R27H, G35S, V95I, R104Q, K126E). We applied both the two-microelectrode voltage clamp technique, using cRNA-injected Xenopus oocytes, and the whole-cell patch clamp technique using transfected HEK293 cells. Surprisingly, four out of the nine mutations did not affect channel properties. Gain-of-function, as typically observed in LQT3 mutant channels, was observed only in R18W and V125L, whereas loss-of-function, frequently found in BrS mutants, was found only in R27H, R104Q, and K126E. Our results indicate that the hNav1.5 N-terminus plays an important role for channel kinetics and stability. At the same time, we suggest that additional mechanisms, as e.g. disturbed interactions of the Na+ channel N-terminus with other proteins, contribute to severe clinical phenotypes.